Designing Mobile Applications for Inquiry-Based Learning in Environmental Science in Madrasah Environment - Mochamad Sukron Amin; Alma Vorfi Lama (Yayasan Avicenna, 2025)
This study aims to analyze the limitations of contextual learning models in environmental science education in madrasahs, explore the potential and challenges of developing mobile applications for inquiry-based learning, and examine students’ responses to using inquiry-based digital media in understanding environmental issues. This study uses a qualitative approach with a case study design. Data collection techniques were carried out through in-depth interviews, participatory observation, and documentation, which were analyzed using data reduction techniques, data display, and verification of findings. The study results indicate that conventional methods still dominate science learning in madrasahs and have not utilized contextual learning optimally. Teachers face challenges in the form of limited infrastructure, digital media, and low technological literacy. However, students responded positively to the interactive mobile application-based approach that supports the inquiry process. The implications of these findings emphasize the need to develop learning applications relevant to the local context and can increase students’ active involvement in understanding environmental issues. This study contributes to the innovation of technology-based science learning models in madrasah environments and as a reference for developing digital-based curricula oriented towards ecological literacy.